Resposta :
Olá!
Explicação passo a passo: Utilizando a fórmula de Bhaskara.
ax²+bx+c=0
x²-5x +6=0
a=1
b= -5
c=6
Δ=b²-4.a.b
Δ=(-5)²-4.(1).(6)
Δ=25-24
Δ=1
x=--b±√Δ /2.a
x= -(-5)±√1 2.1
x= 5±1 /2
x₁=5+1/2=6/2=3
x₂=5-1/2=4/2=2
S={3,2}
![Ver imagem ANDERSONVASCO081](https://pt-static.z-dn.net/files/db9/043b51b81a6c796b14a9c22dd47d18d5.png)
Olá!
Explicação passo a passo: Utilizando a fórmula de Bhaskara.
ax²+bx+c=0
x²-5x +6=0
a=1
b= -5
c=6
Δ=b²-4.a.b
Δ=(-5)²-4.(1).(6)
Δ=25-24
Δ=1
x=--b±√Δ /2.a
x= -(-5)±√1 2.1
x= 5±1 /2
x₁=5+1/2=6/2=3
x₂=5-1/2=4/2=2
S={3,2}